2022
DOI: 10.3390/ijerph191710670
|View full text |Cite
|
Sign up to set email alerts
|

The Social Determinants of Adverse Childhood Experiences: An Intersectional Analysis of Place, Access to Resources, and Compounding Effects

Abstract: Children across all races/ethnicities and income levels experience adverse childhood experiences (ACEs); however, historically excluded children and families must contend with added adversities across ecological levels and within higher-risk conditions due to systemic inequality. In this grounded theory study, the authors examined how health and social service providers (N = 81) from rural and urban counties in Tennessee provided services to low-income families, children exposed to opioids, and children of imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The association which this study found was thus the proximal of the association of local context in childhood with ACEs, as the “ACE Pyramid” suggested that social conditions/local context can produce vulnerability to experience ACEs [ 9 ]. Children in low socioeconomic families tend to have many ACEs due to increased parental stress and limited capacity [ 15 , 32 ] as well as limited access to resources to avoid ACEs [ 8 ]. For mechanism (ii), even if those living in deprived area in adulthood did not live in deprived area in childhood, ACEs may push people to live in deprived area in adulthood, because ACEs negatively affect socioeconomical positions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association which this study found was thus the proximal of the association of local context in childhood with ACEs, as the “ACE Pyramid” suggested that social conditions/local context can produce vulnerability to experience ACEs [ 9 ]. Children in low socioeconomic families tend to have many ACEs due to increased parental stress and limited capacity [ 15 , 32 ] as well as limited access to resources to avoid ACEs [ 8 ]. For mechanism (ii), even if those living in deprived area in adulthood did not live in deprived area in childhood, ACEs may push people to live in deprived area in adulthood, because ACEs negatively affect socioeconomical positions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACEs have negative, lasting effects on mental and physical health and well-being even later in life [ 1 3 ]; such as: cardiovascular disease [ 4 ], depression [ 5 ], diabetes [ 6 ], and cancer [ 7 ]. The significant impacts of systemic inequality in environment, including the social and economic conditions in which they live, learn, work, and play, may affect the vulnerability for adverse experiences, as social determinants of ACEs [ 8 10 ]. Family poverty, low education, less opportunity to work, spirituality, race, parental ACEs, and living conditions are related to increased risk of experiencing ACE(s) [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intertwined with SDoH are adverse childhood experiences (ACEs) such as exposure to violence, abuse or neglect, parental substance abuse, and parental incarceration. While all children have the potential to experience ACEs, youth who also hold marginalized identities or have been continuously excluded, have the layered impact of socially created inequity contributing to the increased likelihood for ACEs exposure (Camacho & Clark Henderson, 2022). There is strong support to suggest that those with exposure to early adverse life events have higher rates of most DGBIs (Bradford et al, 2012; Jones et al, 2013) than those without early exposure.…”
Section: Racism and Discrimination Contributing To Sdohmentioning
confidence: 99%
“…In syndemics, social conditions contribute to disease formation, accumulation, spread, and progression by increasing susceptibility and reducing immune function, particularly among marginalized populations; hence, syndemics are most likely to emerge under conditions of health inequality ( 43 ). A syndemic can be exemplified by the interactions of ACEs, negative social conditions (i.e., SDoH), and risky health behaviors worsening the risk of various chronic health conditions ( 2 , 3 , 44 ). However, an accurate assessment of these complex associations can be methodologically challenging, as the involved risk factors may be highly correlated, interactive, or synergistic.…”
Section: Introductionmentioning
confidence: 99%